Dealing with Noise in Cluster Pattern Interface - Brimkov, Valentin E.; Barneva, Reneta P.; Kanev, Kamen (Combinatorial Image Analysis, 2020)
Cluster Pattern Interface (CLUSPI) [6] is an original 2D encoding and a related technology for direct point-and-click interfaces. It allows determining the objects printed on a surface pointed out by the user. The surface is covered by a layer of code composed of tiny dots, which blends with the original surface texture. In practice, however, some of the dots of the code may be damaged or obscured, which creates decoding challenges. In this work we develop theoretical solutions to some of the challenges related to decoding noisy patterns.